The Development of a Methodology with a Tool Support to the Distributed Simulation of Heterogeneous and Complexes Embedded Systems - Negreiros, Ângelo Lemos Vidal de; Brito, Alisson Vasconcelos (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
Nowadays, embedded systems contains a big computational power and consequently a big complexity. It is very common to find different kinds of applications being executed in embedded systems. With this scenario, it is necessary some method and/or tool that allows the simulation of those systems in an efficient and practice way. The goal of this paper is to expose the integration between Ptolemy II and HLA in order to enable the elaboration of one methodology, with a tool support, to model and simulate large scale heterogeneous embedded systems.